Validations of high-rank syntaxa in Potamogetonetea and Scheuchzerio-Caricetea fuscae - Theurillat, Jean-Paul; Mucina, Ladislav; Hájek, Michal (Lazaroa, 2015)
This paper presents the validation of five syntaxonomic concepts –two orders (Callitricho hamulatae-Ranunculetalia aquatilis, Zannichellietalia pedicellatae) and three alliances (Ranunculion aquatilis, Nelumbion nuciferae and Caricion viridulo-trinervis).